O racjonalnym wykorzystaniu internetu w edukacji - MORBITZER, JANUSZ (Interdyscyplinarne Konteksty Pedagogiki Specjalnej, 2018)
Janusz Morbitzer, On the rational use of the Internet in education, Interdisciplinary Contexts of Special Pedagogy, No. 23, Poznań 2018. Pp. 7–21. Adam Mickiewicz University Press. ISSN 2300-391X. DOI: https://doi.org/10.14746/ikps.2018.23.01 The Internet has become one of the most important educational tools today. However, research shows that it is often used without the necessary reflection, as an easily accessible source of information instead of being a tool for intellectual development. This article presents new opportunities offered by the Internet and new competences that are necessary to fully use the Internet’s potential in education. These competences are mostly intellectual and axiological, not technical.